Characteristics of Intestinal Mucosa-associated Lymphoid Tissue in Experimental Trichinellosis in Rats - O. B. Zhdanova; L. R. Mutoshvili; O. V. Rudneva; N. A. Makarova; L. A. Napisanova; I. I. Okulova; O. V. Chasovskikh; D. S. Novoselov; E. S. Kliukina (Российский паразитологический журнал, 2020)
The purpose of the research is studying intestinal mucosa-associated lymphadenoids (MALT) at trichinellosis. Materials and methods. The number of lymphoid nodules and Peyer’s patches was counted by grossing and microscope slides of intestinal specimen. We investigated their syntopy and morphological traits in Trichinella-infected and control animals. All morphological structures were described in accordance with anatomical, immunological and histological terminology. Results and discussion. The number of lymphoid nodules in the intestinal wall thickness increased by 1.63 times in the experimental group. The changes involved the syntopy of lymphoid tissue. There was an even distribution of lymphoid nodules being concentrated in some segments in the form of Peyer’s patches. The size of the grouped nodules in the experimental trichinellosis increased 1.31 times in the small intestine, and 1.26 times in the straight intestine. It was found that the MALTs were sensitive to the infection. Immunomorphological studies of the MALT should be considered in the development of safe complex drugs, immunostimulants or vaccines. Further, the condition of the MALT should be taken into account in the pathogenesis of trichinellosis along with classical methods such as parasitological (larvae or egg counts), immunological, immunohistochemical or other methods.